Highly Sensitive Refractive Index-Based Sensor for DNA Hybridization Using Subwavelength Grating Waveguide. Issue 6 (2nd November 2022) - Singh, Rukmani; Priye, Vishnu; Chack, Devendra
Abstract : A biosensor for detecting DNA hybridization via refractive index sensing has been demonstrated using a subwavelength grating (SWG) waveguide. Waveguide dimensions are selected by parametric optimizations to increase the mode-analyte overlap with considerations of typical silicon-on-insulator fabrications technology. DNA layer is added with a linker layer on silicon pillars of the SWG waveguide to optimize and detect the DNA hybridization. Some essential characteristics such as mode overlap factor, change in effective refractive index, waveguide sensitivity, and shift in resonance wavelength are computed for the different dimensional parameters of the SWG waveguide in DNA hybridization along with mode field intensity and normalized power using the finite element method. The DNA hybridization is shown by variation in normalized power of interacting light in cladding region of the waveguide for 0% to 100% fractional change of dsDNA and ssDNA. Waveguide sensitivity, shift in resonance wavelength, device sensitivity, and intrinsic limit of detection are obtained to ∼ 0.157, 7.01, 605 nm/RIU, and 1.30 × 10 −4 RIU, respectively, for the optimized structure of SWG waveguide in sensing of DNA hybridization, which could be suitable aspects for detecting DNA hybridization.